pdvsa

asked on

# Sum Per Month

ASKER CERTIFIED SOLUTION

membership

Create an account to see this answer

Signing up is free. No credit card required.

correction to my formula above

=SUMPRODUCT((MONTH($B$3:$KV$3)=MONTH(B$1))*((YEAR($B$3:$KV$3)=YEAR(B$1))*($B$4:$KV$4)))

Sum-Per-Month.xlsx

=SUMPRODUCT((MONTH($B$3:$K

Sum-Per-Month.xlsx

ASKER

Thank you. Rgonzo's accounted for the years which is what I was after. August 2016 and August 2017 were the same answer under Professor's. I might have not made that so clear though.

glad Rgonzo's solution worked for you. i did not notice at first glace your data had multiple years, so i posted a modified formula which is =SUMPRODUCT((MONTH($B$3:$KV$3)=MONTH(B$1))*((YEAR($B$3:$KV$3)=YEAR(B$1))*($B$4:$KV$4))) which works too.

ASKER

Thank you for your follow up. Much appreciated

you are welcome.

=SUMPRODUCT((MONTH($B$3:$K

see attached.

Sum-Per-Month.xlsx